The Effect of Gadget Use on Speech Delay in Children Aged 3-5 Years - Pratiwi Rintang; Nila Widya Keswara (Jurnal Siti Rufaidah, 2025)
Language development in preschool children is an important aspect in supporting children's cognitive, social, and emotional abilities in the future. One environmental factor that is thought to contribute to speech delay is excessive use of gadgets at an early age. This study aims to analyze the effect of gadget use on speech delay in children aged 3–5 years at the Tungoi Community Health Center. This study uses an analytical observational design with a cross-sectional approach. The study sample consisted of 50 children aged 3–5 years who met the inclusion criteria, using consecutive sampling. Data were collected through a questionnaire on gadget use filled out by parents and a screening of children's speech development. Data analysis was performed univariately and bivariately using the Chi-Square test with a significance level of p < 0.05. The results showed that most children used gadgets for more than one hour per day (70%) and more than half of the respondents experienced speech delay (56%). The Chi-Square test showed a significant relationship between gadget use and the occurrence of speech delay (p = 0.000). Children with longer gadget use had a greater risk of speech development delay compared to children with more limited gadget use. The conclusion of this study indicates that gadget use is a significant risk factor for speech delay in children aged 3–5 years. Therefore, it is necessary to limit the duration of gadget use and increase the role of parents and health workers in providing optimal verbal stimulation and assistance to support children's language development.